Rare Case of Cavernous Haemangioma of the Right Atrium with Probable Hepatic Haemangioma - Sally Harrison (Case Reports in Cardiology)
Cardiac haemangiomas are rare causes of atrial masses. This case report is of a 44-year-old male who presented with a right atrial mass that was found incidentally on a CT performed for renal colic. The mass was further investigated with a transthoracic echocardiogram that showed that it was echodense and arising from the Eustachian valve in the right atrium. Coronary angiogram revealed large well-developed atrial branches that crossed superiorly over the left atrium and entered the mass in the right atrium. Surgical resection was undertaken, and this confirmed that the mass had a fleshy, encapsulated appearance with a sessile stalk. Histology demonstrated a cavernous haemangioma. The patient had a residual small defect in the interatrial septum postoperatively but otherwise made a good recovery.